Sejarah Lembaga Pendidikan Musik Klasik Non Formal di Kota Medan - Agung Suharyanto (Gondang: Jurnal Seni dan Budaya, 2017)
Tjong Sce Yin (founder of the first music school in Medan) and Tjong A Fie Mansion (the first school house in Medan) with the name of Medan Music School renamed the Pure Music Institute (LMM) and now renamed the Conservatory Music Medan. In addition to the above three things, also can not be separated from some non-formal music education institutions that organize classical music education in Medan that is Melody Music Studio (Musical Field), Musika Era, Music Rhythm and Institute of Music Education (LPM) Farabi Medan .